Methotrexate impact on radiographic progression in biologic-treated rheumatoid arthritis under clinical remission: A case report on monozygotic Caucasian twins - Soukup, Tomas; Nekvindova, Jana; Dosedel, Martin; Brtkova, Jindra; Toms, Jan; Bastecka, Drahomira; Bradna, Petr; Vlcek, Jiri; Pavek, Petr (International journal of immunopathology and pharmacology, 2016)
We describe Caucasian monozygotic twin brothers with rheumatoid arthritis (RA) and discuss influence of predictors to methotrexate (MTX) outcome treatment. Single nucleotide polymorphisms (SNPs) of the MTX metabolic pathways were genotyped. Twins have multiple mutations: a CC mutation of SNP 1298A>C in methylenetetrahydrofolate reductase (MTHFR) gene, CC mutations of three SNPs in the adenosine receptor gene ADORA2A (rs3761422_4217241T>C, rs2267076_4221164T>C, rs2236624_4226593T>C), and a heterozygous genotype in SNPs ATIC_rs2372536_347C>G, MTHFD1_rs2236225_1958G>A. These mutations are known to predict a worse outcome of MTX treatment. The twins had different lifestyles (alcohol drinking and smoking in Twin 1, regular coffee consumption in Twin 2), but a very similar clinical presentation of the outset of RA, radiographic scoring according to the Sharp/van der Heijde method with an almost identical antibodies presentation. The period of the patients before anti-TNFα treatment was characterized by unsuccessful per oral MTX pharmacotherapy in both cases (a low effect of MTX in Twin 1; an early discontinuation of MTX due to an adverse event in Twin 2). In both twins, the outcome of well-controlled anti-TNFα treatment (co-medication with MTX in Twin 1) for 10 years was expressed as low disease activity measured using composite index DAS28. It is interesting that Twin 2 had an unfavorable radiographic scoring after a 10-year follow-up than Twin 1 in spite of the comparable DAS28 in Twin 2 and smoking in Twin 1. In conclusion, co-medication of MTX with biologics may impact on RA radiographic progression despite predicted bad MTX outcome based on pharmacogenetic analysis.
Keywords: běloši; biologické přípravky; methotrexát; Disease Progression; jednonukleotidový polymorfismus; progrese nemoci; výsledek terapie; Drug Therapy, Combination; Middle Aged; mužské pohlaví; dvojčata monozygotní; twins; pharmacogenetics; Twins, Monozygotic; kombinovaná farmakoterapie; Humans; antirevmatika; Methotrexate; Arthritis, Rheumatoid; lidé středního věku; White People; revmatoidní artritida; Antirheumatic Agents; rheumatoid arthritis; methotrexate; Biological Products; Treatment Outcome; lidé; Male; Polymorphism, Single Nucleotide